On the dispersion characteristics of relativistic obliquely propagating Bernstein wave in a degenerate electron plasma - S. Noureen; G. Abbas; M. Sarfraz; Muddasir Ali (AIP Advances, 2018)
The dispersion characteristics of obliquely propagating electrostatic Bernstein wave in a relativistic degenerate electron plasma is markedly different from perpendicular one. Employing linearized Vlasov-Maxwell model, the dispersion relation of obliquely propagating Bernstein wave in a relativistic degenerate electron plasma is derived. In particular, the results are obtained in the propagation range kz > kx with kx≠0. In the high frequency (ω > > k.v) and weak propagation (Ω>>k.v or k → 0) limiting cases, the generalized results reduce to the Upper hybrid wave for θ′ = 00 and Langmuir wave for θ′ = 900 (where Ω is the gyro-frequency and θ′ is the propagation angle of k with respect to x-axis). Graphical analysis is also performed to highlight the new trends in wave spectra.